Multidisciplinary design process observations of a "train front cab cleaning robot" project - Taykaldiranian, Gerard (Cranfield University, 2017)
This thesis presents an observation of the designed development process of a train cab front cleaning robot that was demonstrated by building a scaled prototype which was presented during the robotics and autonomous systems dissemination event held by RRUKA. The design process consisted of the systems, mechanical, and software designs which were completed in a multidisciplinary engineering project. Self-reflective observation was conducted to identify problems in decision making, lack of expertise which led to delays, cost increase of the project. The challenges of a multidisciplinary academic design project were addressed during the integration phase when all the system came together in order to build the robot. The problems faced during the project were categorised into external, managerial, logistical, and design issues, which were in turn analysed through.
Keywords: Robot design; self-reflection observation; systems integration; academic design challenges; design process; multidisciplinary